2023
DOI: 10.1080/07853890.2023.2200258
|View full text |Cite
|
Sign up to set email alerts
|

In silico and in vivo demonstration of the regulatory mechanism of Qi-Ge decoction in treating NAFLD

Abstract: Background Nonalcoholic fatty liver disease (NAFLD), a chronic and progressive liver disease, often causes steatosis and steatohepatitis. Qi-Ge decoction (QGD) shows a good effect against NAFLD in the clinic. But the molecular mechanism for QGD in improving NAFLD is unknown. Purpose This study explored the molecular mechanism of QGD in NAFLD model rats using comprehensive network pharmacology, molecular docking and in vivo verification strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Differential gene expression analysis was conducted using DESeq [ 58 ], and differentially expressed genes (DEGs) were defined based on the following criteria: |log 2 fold change|> 1 and the P value < 0.05. The DEGs were subjected to functional annotation and pathway enrichment analysis using the KOBAS server [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…Differential gene expression analysis was conducted using DESeq [ 58 ], and differentially expressed genes (DEGs) were defined based on the following criteria: |log 2 fold change|> 1 and the P value < 0.05. The DEGs were subjected to functional annotation and pathway enrichment analysis using the KOBAS server [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary research has established a QG fingerprint (Ke et al, 2017), determined the optimal ratio and extraction process (Huang et al, 2017;Li, 2016), identified its main components (Li et al, 2022;Yu et al, 2021), and confirmed its pharmacological efficacy (Zhou, 2021;Zhou et al, 2021;Zhu, 2019). QG has lipid-lowering and hepatoprotective effects in hyperlipidemic rats (Fan et al, 2022(Fan et al, , 2023Peng et al, 2019Peng et al, , 2023, but its effective substances and their targets of action remain unclear.…”
Section: Introductionmentioning
confidence: 99%